Preparation method and device of catalyst slurry
Through the combination of high-speed dispersion pretreatment and high-pressure dispersion treatment, the problem of insufficient uniformity and stability in the preparation of catalyst slurry is solved, and the electrochemical performance of high-quality catalytic layer and membrane electrode is improved, which is suitable for continuous mass production.
Patent Information
- Application Number
- CN202411843146.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing catalyst slurry preparation methods cannot process high solid content and large volume slurry, resulting in poor uniformity and stability of the catalytic layer, affecting the electrochemical performance of the membrane electrode.
By combining high-speed dispersion pretreatment and high-pressure dispersion treatment, a solid-liquid mixed phase is formed by mixing an ionomer solution, an organic dispersant and a medium boiling point solvent, and multiple cycles of dispersion and grinding are performed in a high-pressure grinding drum to ensure the uniformity and stability of the catalyst slurry.
The preparation of catalyst slurry with high uniformity and high stability is achieved, and the electrochemical performance of the membrane electrode and the quality of the catalytic layer are improved, which is suitable for continuous mass production.
Smart Images

Figure CN119656944A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of PEM water electrolysis hydrogen production, and in particular to a method and device for preparing catalyst slurry. Background Art
[0002] Hydrogen energy has many advantages such as cleanliness, sustainability and high efficiency, and has great development prospects. Hydrogen energy research mainly includes three aspects: production, storage, transportation and use. PEM water electrolysis is a green hydrogen production technology. It uses pure water and is environmentally friendly. It has high current density, working efficiency and gas purity, and adapts to the volatility of renewable energy generation. In terms of clean and efficient hydrogen use, PEM fuel cells convert chemical energy into electrical energy through chemical reactions, and are one of the most promising alternatives to improve energy efficiency and reduce carbon emissions. The membrane electrode is the core component of the PEM electrolysis hydrogen production stack and the fuel cell stack. The catalyst layer of the membrane electrode is the main place for electrochemical reactions and material energy conversion in the stack, which has an important influence on the performance of the stack. The catalyst layer is usually formed by applying the catalyst slurry on both sides of the proton exchange membrane by spraying or coating. The composition and preparation process of the catalyst slurry is one of the most important links in the entire membrane electrode production process, which directly affects the quality of the catalyst layer and the electrochemical performance of the membrane electrode.
[0003] The traditional method of preparing catalyst slurry mainly utilizes high-power ultrasonic dispersion process to disperse the slurry mixture. Due to its limited dispersion ability, this method cannot handle high solid content and large volume slurry. The dispersion method of catalyst slurry with high solid content is particularly important. In view of the influence of catalyst slurry on the coating quality of the catalytic layer and the electrochemical performance of the membrane electrode, the influence of the composition of catalyst slurry on the catalytic layer forming process and the uniformity and stability of the slurry's own dispersion are all key points that need to be considered.
[0004] In recent years, with the demand for continuous batch preparation technology of membrane electrode catalyst layer, the dispersion method of high solid content catalyst slurry has become particularly important. In view of the influence of catalyst slurry on the coating quality of catalyst layer and the electrochemical performance of membrane electrode, the influence of the composition of catalyst slurry on the catalyst layer forming process and the uniformity and stability of the slurry's own dispersion are all key points that need to be considered.
[0005] At present, catalyst slurries suitable for coating processes are generally dispersed in the form of high-speed shear dispersion such as mechanical stirring, planetary stirring and high-speed disperser. The catalyst slurries dispersed by this method have poor uniformity, especially when the volume of slurry to be processed is relatively large. The slurry cannot be fully dispersed in the area far away from the dispersion center, and the ionomers and catalyst particles in the slurry are prone to form larger agglomerates. The uniformity and stability of the slurry are poor, which is not conducive to the subsequent catalytic layer coating, nor is it conducive to the full exertion of the catalyst activity. The slurry preparation efficiency is low. The process will also generate high heat input and a large number of bubbles in the slurry. The high temperature during the dispersion process will aggravate the agglomeration of catalyst particles, resulting in the inability to obtain a high-quality catalytic layer.
[0006] In addition, there is also a vacuum homogenization process for dispersing high-solid content slurries. This method requires a long period of ultrasonic dispersion, magnetic stirring, high-speed shear dispersion, etc. (to avoid clogging of the homogenization chamber during homogenization), and then vacuum homogenization dispersion and degassing. This method has many slurry dispersion steps, requires a long time, has low slurry preparation efficiency, and a small volume of slurry processed at a single time. The uniformity of slurries prepared in different batches cannot be guaranteed, and it cannot match the high-consistency batch production of membrane electrode catalyst layers. Summary of the invention
[0007] The purpose of the present invention is to provide a method and device for preparing a catalyst slurry with high uniformity and high stability for continuous batch production needs, overcome the above-mentioned defects of the existing catalyst slurry preparation technology, and thus obtain a high-quality coated catalytic layer and higher membrane electrode electrochemical performance.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows:
[0009] One aspect of the present invention provides a method for preparing a catalyst slurry, comprising the following steps:
[0010] (1) mixing an ionomer solution with an organic dispersant and a medium boiling point solvent to obtain a mixed solution;
[0011] (2) mixing the catalyst with ultrapure water, then adding the mixed solution obtained in step (1), and performing high-speed dispersion pretreatment at a rotation speed of 5000-8000 rpm to obtain a primary catalyst slurry;
[0012] (3) subjecting the primary catalyst slurry obtained in step (2) to a high-pressure dispersion treatment, wherein the pressure of the high-pressure dispersion is 25,000-35,000 psi, and grinding at 3-8° C. after the high-pressure dispersion;
[0013] (4) After the grinding of the primary catalyst slurry, step (3) is repeated for 3-5 cycles to obtain the catalyst slurry.
[0014] In the above technical solution, further, the solid content of the catalyst slurry is 5%-25%;
[0015] In the catalyst slurry, the mass ratio of ionomer resin to catalyst is (0.2-0.6):1;
[0016] In the catalyst slurry, the mass ratio of ultrapure water, organic dispersant and medium boiling point solvent is (45-60):(30-50):(3-10);
[0017] The mass concentration of the ionomer solution is 5%-20%.
[0018] In the above technical solution, further, in step (1), the medium boiling point solvent is one of n-butanol, toluene and cyclohexanone;
[0019] The organic dispersant is one of isopropanol, ethanol and n-propanol.
[0020] In the above technical solution, further, in step (2), the high-speed dispersion pretreatment is carried out using a high-speed disperser, and the pre-dispersion time is 10-30 minutes.
[0021] Another aspect of the present invention provides a device used in the method for preparing the catalyst slurry, comprising a grinding drum containing zirconium oxide beads, wherein a feed end and a discharge end are respectively provided on the grinding drum, wherein a feed cavity is provided at the feed end, a high-pressure pushing mechanism is provided in the feed cavity, a screen is provided in the feed cavity near the feed end of the grinding drum, and the screen is rotatably connected in the grinding drum; the discharge end of the grinding drum is connected to the feed cavity through a pipeline;
[0022] The grinding drum body comprises an outer body and an inner body, a hollow cavity is formed between the outer body and the inner body, and a cooling circulating water pipe is arranged in the hollow cavity.
[0023] In the above technical solution, further, the cooling circulation water pipe is surrounded in the hollow cavity and attached to the outer wall of the inner cylinder or the inner wall of the outer cylinder.
[0024] In the above technical solution, further, the pore size of the sieve is 100-200 microns.
[0025] The present invention also provides a method for preparing catalyst slurry using the above device, characterized in that it comprises the following steps:
[0026] S1, mixing the ionomer solution with an organic dispersant and a medium boiling point solvent to obtain a mixed solution;
[0027] S2, mixing the catalyst with ultrapure water, and then adding the mixed solution to perform high-speed dispersion pretreatment to obtain a primary catalyst slurry; wherein the speed of the high-speed dispersion pretreatment is 5000-8000 rpm;
[0028] S3, placing the primary catalyst slurry into the feed cavity of the grinding drum containing zirconium oxide beads, pushing the primary catalyst slurry to the screen by a high-pressure pushing mechanism, and controlling the rotation of the screen to achieve the cutting and dispersion of particle agglomerates in the catalyst slurry, and the catalyst slurry enters the grinding drum after high-pressure dispersion, and the zirconium oxide beads grind the catalyst slurry while the grinding drum rotates, and the grinding is performed at 3-8°C;
[0029] S4, the primary catalyst slurry after grinding enters the feed chamber again through the pipe at the discharge end, and the catalyst slurry is obtained after repeating step S3 for 3-5 cycles.
[0030] In the above technical solution, further, in step S1, the medium boiling point solvent is one of n-butanol, toluene and cyclohexanone;
[0031] The organic dispersant is one of isopropanol, ethanol and n-propanol.
[0032] In the above technical solution, further, in step S3, the pressure of the high-pressure pushing mechanism is 20000-35000psi;
[0033] The rotation speed of the screen is 2000-5000rpm;
[0034] The size of the zirconia beads is 0.1-0.5 mm, the rotation speed of the grinding chamber is 3000-4000 rpm, and the grinding processing time is 15-40 minutes.
[0035] In the above technical solution, further, in step S4, in each cycle, the rotation speed of the screen is 1.05-1.3 times that of the previous cycle;
[0036] In each cycle, the pressure of the high-pressure pushing mechanism increases by 3000psi compared with the previous cycle.
[0037] In summary, the present invention has the following beneficial effects:
[0038] 1. The present invention first disperses the ionomer into the organic dispersant by ordinary mixing to avoid agglomeration with the catalyst powder in the later mixing, and then forms a solid-liquid mixed phase by high-speed dispersion to avoid solid-state deposition that causes the subsequent inability to further process the entire catalyst slurry. That is, the solid-liquid mixed phase can facilitate high-pressure grinding and dispersion of the entire catalyst slurry to facilitate fine dispersion;
[0039] 2. A certain amount of medium-boiling-point solvent is added during the preparation of the catalyst slurry. Since the mixing method of the present invention adopts high speed and high pressure, the addition of the medium-boiling-point solvent during this process can reduce the evaporation of the medium-boiling-point solvent under the temperature increase environment of the mixing method of the present invention. Reducing the evaporation is beneficial to the performance guarantee of the catalyst slurry in the process of multiple circulation dispersion. Secondly, when the slurry is used to coat the membrane electrode catalyst layer, it can avoid the dispersion and segregation of catalyst particles when only water is left in the late drying stage and the generation of cracks in the catalyst layer, which affects the electrochemical performance of the membrane electrode, and no inactive materials will be introduced into the catalyst layer after drying. That is, the present invention adds a medium-boiling-point additive under the mixing method of the present invention according to the characteristics of the catalyst slurry, which can effectively reduce the impact on the performance of the catalyst slurry under the high-speed, high-pressure and high-temperature environment;
[0040] 3. The present invention controls the slurry temperature during the grinding process to avoid high temperature, thereby avoiding the agglomeration of catalyst particles and ionomers in the slurry, which is conducive to obtaining a high-quality catalyst layer and achieving high electrochemical performance;
[0041] 4. The catalyst slurry is prepared by the method of the present invention without the need for an additional degassing process. The trace bubbles generated during the pre-dispersion process can be eliminated during the high-pressure grinding process, and the overall dispersion process steps of the slurry are simplified.
[0042] 5. The present invention provides a device for catalyst slurry, which first pushes the catalyst slurry to the screen by high-pressure pushing, and controls the rotation of the screen to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry, and then the dispersed catalyst slurry is evenly refined through the gaps of the grinding medium in the grinding drum, and finally the cutting, dispersion and grinding and refining are performed continuously and multiple times through the circulation pipeline to ensure that the particle size in the catalyst slurry is small and uniform; that is, through the grinding device designed by the present invention, the total dispersion time can be controlled at about 1 hour, which greatly improves the dispersion efficiency of the slurry, and the catalyst slurry prepared by the method is evenly refined through the gaps of the grinding medium, the slurry particle size D50 is stable between 100-150nm, and the viscosity of the catalyst slurry is 120-260mPa·s, which can well meet the requirements of the membrane electrode catalyst layer coating process;
[0043] 6. The catalyst slurry is prepared by the device and method of the present invention. Since a continuous cycle grinding process can be performed, continuous batch preparation can be achieved. There is no limit on the total volume of the slurry, so it is more applicable. Moreover, samples can be taken for testing at any time during the slurry dispersion process without affecting the dispersion process. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram of the overall structure of the device used for preparing the catalyst slurry of the present invention;
[0045] Figure 2 It is a schematic diagram of the structure of the cooling circulating water pipe provided in the grinding drum;
[0046] Figure 3 The catalyst layer surface prepared in Example 2;
[0047] Figure 4 The surface of the catalyst layer prepared in Comparative Example 1;
[0048] Figure 5 The surface of the catalyst layer prepared in Comparative Example 3;
[0049] In the figure: 1. Grinding drum; 1-1. Feed chamber; 1-2. Inner cylinder; 1-3. Outer cylinder; 2. High-pressure pushing mechanism; 3. Screen; 4. Circulation pipeline; 5. Raw material barrel; 6. Storage barrel; 7. Discharge pipe; 8. Feed pipe; 9. Cooling circulation water pipe; 10. Coolant delivery pipe; 11. Coolant water tank. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below with reference to the accompanying drawings. Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0051] The structure of the device used in the preparation of catalyst slurry of the present invention is as follows Figure 1 As shown, it includes a grinding drum 1 filled with zirconium oxide beads. The grinding drum 1 is mechanically designed based on existing technology to realize the rotation of the drum body; a feeding end and a discharging end are respectively provided on the grinding drum 1, and a feeding cavity 1-1 is provided at the feeding end. A high-pressure pushing mechanism 2 is provided in the feeding cavity 1-1. The high-pressure pushing mechanism 2 adopts a commonly used sealed piston type to realize the pushing in the feeding cavity 1-1, and is combined with the drive of a hydraulic cylinder or a cylinder to realize the electric pushing process. A screen 3 is provided in the feeding cavity 1-1 near the feeding end of the grinding drum 1, and the screen 3 is connected to the bearing The grinding drum 1 is rotatably connected to the grinding drum 1 by conventional mechanical connection means in the art, and is driven by a high-speed motor to rotate at high speed in the grinding drum 1; in addition, a circulation pipe 4 is connected to the discharge end at the bottom of the grinding drum 1, and the end of the circulation pipe 4 away from the discharge end is connected to the feed chamber 1-1, and the discharge end at the bottom of the grinding drum 1 is connected to a storage barrel 6 through a discharge pipe 7, and the feed chamber 1-1 of the grinding drum 1 is connected to a raw material barrel 5 through a feed pipe 8. The circulation pipe, the feed pipe 8, and the discharge pipe 7 are all provided with electric switch valves to control the opening and closing of the pipes;
[0052] Further, such as Figure 1 and 2As shown, the grinding drum body includes an outer cylinder 1-3 and an inner cylinder 1-2, and a hollow cavity is formed between the outer cylinder 1-3 and the inner cylinder 1-2. A cooling circulation water pipe 9 is arranged in the hollow cavity. The cooling circulation water pipe 9 surrounds the outer wall of the inner cylinder 1-2 or the inner wall of the outer cylinder 1-3. The cooling circulation water pipe 9 is connected to an external cooling liquid tank 11 through a cooling liquid delivery pipe 10.
[0053] Example 1
[0054] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0055] S2, 50g of Pt / C catalyst powder with a Pt loading of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of the high-speed dispersion pretreatment was 5000rpm, and a primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of the ionomer resin to the catalyst in the slurry was 0.5:1;
[0056] S3, dispersing the primary catalyst slurry under a high pressure of 25000 psi and grinding at a temperature of 5° C.;
[0057] S4. The primary catalyst slurry after grinding is dispersed again under a high pressure of 25000 psi for 3 cycles to obtain a catalyst slurry.
[0058] The catalyst slurry prepared in Example 1 was tested using a particle size analyzer, and the results were as follows:
[0059] Table 1
[0060] Particle size and viscosity D50 Viscosity At the end of dispersion 147nm 256mPa·s After 8 hours of inactivity 160nm 260mPa·s
[0061] The slurry prepared in Example 1 was used to prepare a fuel cell membrane electrode. The surface structure of the membrane electrode catalyst layer was intact without defects such as cracks. The performance of the membrane electrode reached: 0.675V@2000mA / cm 2 .
[0062] Example 2
[0063] The specific steps of preparing the catalyst slurry using the above device are as follows:
[0064] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0065] S2, 50g of Pt / C catalyst powder with a Pt loading of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0066] S3, putting the primary catalyst slurry into the raw material barrel 5 of the above-mentioned grinding device. In this embodiment, the mesh 3 of the grinding device has an aperture of 100 μm. Zirconia beads with a size of 0.5 mm are filled into the grinding drum 1. The primary catalyst slurry in the raw material barrel 3 is transported to the feed cavity 1-1. The rotation speed of the mesh 3 is controlled to be 3000 rpm. At the same time, the primary catalyst slurry is pushed to the mesh 3 by the high-pressure pushing mechanism 2 with a pushing force of 25000 psi to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry. After the high-pressure dispersion, the catalyst slurry enters the grinding drum 1, and the grinding drum 1 rotates at a speed of 3000 rpm to achieve the grinding of the primary catalyst slurry by the zirconia beads for 20 minutes. At the same time, during the grinding process, the cooling water of 5°C needs to be continuously circulated through the cooling circulating water pipe 9 to control the temperature of the catalyst slurry in the grinding drum 1.
[0067] S4. After step S3, the primary catalyst slurry after grinding enters the feed chamber 1-1 again through the circulation pipe 4. After repeating step S3 for 3 cycles, the catalyst slurry is obtained. In step S4, the rotation speed of the screen 3 during the second cycle is 3150 rpm, and the pressure of the high-pressure pushing mechanism 2 is 28000 psi; the rotation speed of the screen 3 during the third cycle is 3310 rpm, and the pressure of the high-pressure pushing mechanism 2 is 31000 psi.
[0068] The catalyst slurry prepared in Example 2 was tested using a particle size analyzer, and the results were as follows:
[0069] Table 2
[0070] Particle size and viscosity D50 Viscosity At the end of dispersion 114nm 132mPa·s After 8 hours of inactivity 126nm 147mPa·s
[0071] The slurry prepared in Example 2 was used to prepare a fuel cell membrane electrode, and the surface structure of the membrane electrode catalyst layer was complete. Figure 3 As shown, there are no defects such as cracks, and the performance of the membrane electrode reaches: 0.682V@2000mA / cm 2 .
[0072] Example 3
[0073] The specific steps of preparing the catalyst slurry using the above device are as follows:
[0074] S1. Prepare a mixed solution: weigh 300 g of a Nafion solution with a mass concentration of 10%, weigh 112.50 g of an organic dispersant ethanol, and 12.50 g of a toluene additive, and mechanically stir the mixed solution;
[0075] S2, 100g of 50% Pt / C catalyst powder was mixed with 125g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed. The pre-dispersion treatment time was 30min, and the speed of the high-speed dispersion pretreatment was 8000rpm to obtain a primary catalyst slurry. The solid content of the slurry was 20%, and the mass ratio of the ionomer resin to the catalyst in the slurry was 0.3:1;
[0076] S3, putting the primary catalyst slurry into the raw material barrel 5 of the grinding device. In this embodiment, the mesh 3 of the grinding device has an aperture of 200 μm. Zirconia beads with a size of 0.2 mm are filled into the grinding drum 1. The primary catalyst slurry in the raw material barrel 5 is transported to the feed cavity 1-1. The rotation speed of the mesh 3 is controlled to be 2000 rpm. At the same time, the primary catalyst slurry is pushed to the mesh by the high-pressure pushing mechanism 2 with a pushing force of 20,000 psi to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry. After the high-pressure dispersion, the catalyst slurry enters the grinding drum 1, and the grinding drum 1 rotates at a speed of 4000 rpm to achieve the grinding of the primary catalyst slurry by the zirconia beads for 40 minutes. At the same time, during the grinding process, the cooling water of 5°C needs to be continuously circulated through the cooling circulating water pipe 9 to control the temperature of the catalyst slurry in the grinding drum 1.
[0077] S4. After step S3, the primary catalyst slurry after grinding is re-entered into the feed chamber 1-1 through the circulation pipe 4. After repeating step S3 for 5 cycles, the catalyst slurry is obtained. In step S4, the rotation speed of the screen 3 during the second cycle is 2500rpm, and the pressure of the high-pressure pushing mechanism 2 is 23000psi; the rotation speed of the screen 3 during the third cycle is 3100rpm, and the pressure of the high-pressure pushing mechanism 2 is 28000psi; the rotation speed of the screen 3 during the fourth cycle is 3800rpm, and the pressure of the high-pressure pushing mechanism 2 is 31000psi; the rotation speed of the screen 3 during the fifth cycle is 4700rpm, and the pressure of the high-pressure pushing mechanism 2 is 34000psi.
[0078] The catalyst slurry prepared in Example 3 was tested, and the results were as follows:
[0079] Table 3
[0080] Particle size and viscosity D50 Viscosity At the end of dispersion 105nm 120mPa·s After 8 hours of inactivity 115nm 131mPa·s
[0081] The slurry prepared in Example 3 was used to prepare a fuel cell membrane electrode. The membrane electrode catalyst layer showed a complete structure without defects such as cracks. The performance of the membrane electrode reached: 0.679V@2000mA / cm 2 .
[0082] Example 4
[0083] The catalyst slurry is prepared by using the above device, except that the screen does not rotate. The specific steps are as follows:
[0084] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0085] S2, 50g of Pt / C catalyst powder with a loading amount of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0086] S3, putting the primary catalyst slurry into the raw material barrel 5 of the present grinding device, the mesh 3 of the grinding device in this embodiment has an aperture of 100 μm, filling the grinding drum 1 with zirconia beads of 0.5 mm in size, conveying the primary catalyst slurry in the raw material barrel 5 to the feed chamber 1-1, and using the high-pressure pushing mechanism 2 to push the primary catalyst slurry to the mesh 3 with a pushing force of 40,000 psi to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry, and the catalyst slurry enters the grinding drum 1 after high-pressure dispersion, and the grinding drum 1 rotates at a speed of 3,000 rpm to achieve the grinding of the primary catalyst slurry by the zirconia beads for 20 minutes, and at the same time, during the grinding process, it is necessary to continuously circulate cooling water of 5°C through the cooling circulating water pipe 9 to control the catalyst slurry temperature in the grinding drum 1;
[0087] S4. After step S3, the primary catalyst slurry after grinding enters the feed chamber 1-1 again through the circulation pipe 4. After repeating step S3 for 3 cycles, the catalyst slurry is obtained. During the second cycle of step S4, the pressure of the high-pressure pushing mechanism 2 is 43000psi; during the third cycle, the pressure of the high-pressure pushing mechanism 2 is 46000psi.
[0088] The catalyst slurry prepared in Example 4 was tested, and the results were as follows:
[0089] Table 4
[0090] Particle size and viscosity D50 Viscosity At the end of dispersion 206nm 156mPa·s After 8 hours of inactivity 244nm 187mPa·s
[0091] Example 5
[0092] The catalyst slurry is prepared by using the above device, except that the screen speed and the pushing pressure remain unchanged during the cyclic dispersion in step S4. The specific steps are as follows:
[0093] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0094] S2, 50g of Pt / C catalyst powder with a loading amount of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0095] S3, putting the primary catalyst slurry into the raw material barrel 5 of the present grinding device, the mesh 3 of the grinding device in this embodiment has an aperture of 100 μm, filling the grinding drum 1 with zirconia beads of 0.5 mm in size, conveying the primary catalyst slurry in the raw material barrel 5 to the feed chamber 1-1, controlling the rotation speed of the mesh 3 to be 3000 rpm, and at the same time, using the high-pressure pushing mechanism 2 to push the primary catalyst slurry to the mesh 3 with a pushing force of 40,000 psi to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry, and the catalyst slurry enters the grinding drum 1 after high-pressure dispersion, and the grinding drum 1 rotates at a speed of 3000 rpm to achieve the grinding of the primary catalyst slurry by the zirconia beads for 20 minutes, and at the same time, during the grinding process, it is necessary to continuously circulate cooling water of 5°C through the cooling circulating water pipe 9 to control the temperature of the catalyst slurry in the grinding drum 1;
[0096] S4. After step S3, the primary catalyst slurry after grinding enters the feed chamber 1-1 again through the circulation pipe 4. After repeating step S3 for 3 cycles, the catalyst slurry is obtained. The rotation speed of the screen 3 and the pressure of the high-pressure pushing mechanism 2 remain unchanged in each cycle.
[0097] The catalyst slurry prepared in Example 5 was tested, and the results were as follows:
[0098] Table 5
[0099] Particle size and viscosity D50 Viscosity At the end of dispersion 193nm 141mPa·s After 8 hours of inactivity 228nm 166mPa·s
[0100] Comparative Example 1
[0101] The catalyst slurry is prepared by using the above device, except that the primary catalyst slurry is not pushed under high pressure, but is directly transported under the condition of a rotating screen. The specific steps are as follows:
[0102] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0103] S2, 50g of Pt / C catalyst powder with a loading amount of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0104] S3, put the primary catalyst slurry into the raw material barrel 5 of the grinding device, the mesh 3 of the grinding device has an aperture of 100 μm, fill the grinding drum 1 with zirconia beads of 0.5 mm in size, and transport the primary catalyst slurry in the raw material barrel 5 to the feed cavity 1-1, control the rotation speed of the mesh 3 to 3000 rpm, and let the primary catalyst slurry pass through the mesh and enter the grinding drum by the weight of the slurry, and the grinding drum 1 rotates at a speed of 3000 rpm to grind the primary catalyst slurry with the zirconia beads for 20 minutes. At the same time, during the grinding process, the cooling water of 5°C needs to be continuously circulated through the cooling circulating water pipe 9 to control the catalyst slurry temperature in the grinding drum 1;
[0105] S4. After step S3, the primary catalyst slurry after grinding is re-entered into the feed chamber 1-1 through the circulation pipe 4. After repeating step S3 for 3 cycles, the catalyst slurry is obtained. The rotation speed of the screen 3 during the second cycle of S4 is 3150rpm; the rotation speed of the screen 3 during the third cycle is 3310rpm.
[0106] The catalyst slurry prepared in Comparative Example 1 was tested, and the results were as follows:
[0107] Table 6
[0108] Particle size and viscosity D50 Viscosity At the end of dispersion 364nm 225mPa·s After 8 hours of inactivity 426nm 278mPa·s
[0109] Comparative Example 2
[0110] The catalyst slurry is prepared by using the above device, except that the grinding and dispersion is performed once, and no cyclic dispersion is performed. The specific steps are as follows:
[0111] S1. Prepare a mixed solution: weigh 250 g of a Nafion solution with a mass concentration of 10%, 540 g of an organic dispersant ethanol, and 60 g of a n-butanol additive, and mix them by mechanical stirring;
[0112] S2, 50g of Pt / C catalyst powder with a loading amount of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0113] S3, the primary catalyst slurry is placed in the raw material barrel 5 of the grinding device. In this embodiment, the mesh 3 of the grinding device has an aperture of 100 μm. Zirconia beads with a size of 0.5 mm are filled into the grinding drum 1. The primary catalyst slurry in the raw material barrel 5 is transported to the feed cavity 1-1, and the rotation speed of the mesh 3 is controlled to be 3000 rpm. At the same time, the high-pressure pushing mechanism 2 uses a pushing force of 40,000 psi to push the primary catalyst slurry to the mesh 3 to achieve cutting and dispersion of particle agglomerates in the catalyst slurry. After high-pressure dispersion, the catalyst slurry enters the grinding drum 1, and the grinding drum 1 rotates at a speed of 3000 rpm to achieve zirconia beads grinding the primary catalyst slurry for 20 minutes. At the same time, during the grinding process, it is necessary to continuously circulate cooling water of 5°C through the cooling circulating water pipe 9 to control the catalyst slurry temperature in the grinding drum 1. After this step is completed, the catalyst slurry is obtained.
[0114] The catalyst slurry prepared in Comparative Example 2 was tested, and the results were as follows:
[0115] Table 7
[0116] Particle size and viscosity D50 Viscosity At the end of dispersion 248nm 173mPa·s After 8 hours of inactivity 303nm 213mPa·s
[0117] Comparative Example 3
[0118] The catalyst slurry is prepared by using the above device, except that: no medium boiling point additive is added to the catalyst slurry, and the specific steps are as follows: S1, preparing a mixed solution: weighing 250g of Nafion solution with a mass concentration of 10% and weighing 540g of organic dispersant ethanol, and mixing them by mechanical stirring;
[0119] S2, 50g of Pt / C catalyst powder with a loading amount of 50wt% was mixed with 600g of ultrapure water, and then the mixed solution was added and high-speed dispersion pretreatment was performed, the pre-dispersion treatment time was 10min, the speed of high-speed dispersion pretreatment was 5000rpm, and primary catalyst slurry was obtained, the solid content of the slurry was 5%, and the mass ratio of ionomer resin to catalyst in the slurry was 0.5:1;
[0120] S3, putting the primary catalyst slurry into the raw material barrel 5 of the present grinding device, the mesh 3 of the grinding device in this embodiment has an aperture of 100 μm, filling the grinding drum 1 with zirconia beads of 0.5 mm in size, conveying the primary catalyst slurry in the raw material barrel 5 to the feed chamber 1-1, controlling the rotation speed of the mesh 3 to be 3000 rpm, and at the same time, using the high-pressure pushing mechanism 2 to push the primary catalyst slurry to the mesh 3 with a pushing force of 40,000 psi to achieve the cutting and dispersion of the particle agglomerates in the catalyst slurry, and the catalyst slurry enters the grinding drum 1 after high-pressure dispersion, and the grinding drum 1 rotates at a speed of 3000 rpm to achieve the grinding of the primary catalyst slurry by the zirconia beads for 20 minutes, and at the same time, during the grinding process, it is necessary to continuously circulate cooling water of 5°C through the cooling circulating water pipe 9 to control the temperature of the catalyst slurry in the grinding drum 1;
[0121] S4. After step S3, the primary catalyst slurry after grinding is re-entered into the feed chamber 1-1 through the circulation pipe 4. After repeating step S3 for 3 cycles, the catalyst slurry is obtained. In step S4, the rotation speed of the screen 3 during the second cycle is 3150 rpm, and the pressure of the high-pressure pushing mechanism 2 is 43000 psi; the rotation speed of the screen 3 during the third cycle is 3310 rpm, and the pressure of the high-pressure pushing mechanism 2 is 46000 psi.
[0122] The catalyst slurry prepared in Comparative Example 3 was tested, and the results were as follows:
[0123] Table 8
[0124] Particle size and viscosity D50 Viscosity At the end of dispersion 215nm 162mPa·s After 8 hours of inactivity 246nm 195mPa·s
[0125] The preparation method used in Comparative Example 1 does not implement high-pressure pushing of the primary catalyst slurry, but directly transports the primary catalyst slurry under the condition of rotating the screen. At this time, the dispersed particle size is larger, and the D50 particle size is 364nm. In addition, the slurry contains bubbles, and cracks are generated on the surface of the prepared catalyst layer, such as Figure 4 shown.
[0126] The screen of the device used in Example 4 does not rotate, the uniformity of dispersion is poor, and the particle size is large, with a D50 particle size of 206 nm.
[0127] In Example 5, the screen rotation speed and the pushing pressure remain unchanged during the cyclic dispersion, but the dispersion uniformity is poor and the particle size is relatively large, with a D50 particle size of 193 nm.
[0128] Comparative Example 2 was ground and dispersed only once, the uniformity of dispersion was poor, and the particle size was large, with a D50 particle size of 248 nm.
[0129] In Comparative Example 3, no medium boiling point additive was added to the catalyst slurry, and the prepared catalyst layer had agglomeration of the catalyst, such as Figure 5 shown.
[0130] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a catalyst slurry, characterized in that: The following steps are involved: (1) mixing an ionomer solution with an organic dispersant and a medium boiling point solvent to obtain a mixed solution; (2) mixing the catalyst with ultrapure water, then adding the mixed solution obtained in step (1), and performing high-speed dispersion pretreatment at a rotation speed of 5000-8000 rpm to obtain a primary catalyst slurry; (3) subjecting the primary catalyst slurry obtained in step (2) to a high-pressure dispersion treatment, wherein the pressure of the high-pressure dispersion is 25,000-35,000 psi, and grinding at 3-8° C. after the high-pressure dispersion; (4) After the grinding of the primary catalyst slurry, step (3) is repeated for 3-5 cycles to obtain the catalyst slurry.
2. The preparation method according to claim 1, characterized in that: The solid content of the catalyst slurry is 5%-25%; In the catalyst slurry, the mass ratio of ionomer resin to catalyst is (0.2-0.6):1; In the catalyst slurry, the mass ratio of ultrapure water, organic dispersant and medium boiling point solvent is (45-60):(30-50):(3-10); The mass concentration of the ionomer solution is 5%-20%.
3. The preparation method according to claim 1, characterized in that: In step (1), the medium boiling point solvent is one of n-butanol, toluene and cyclohexanone; The organic dispersant is one of isopropanol, ethanol and n-propanol; In step (2), the high-speed dispersion pretreatment is carried out using a high-speed disperser, and the pre-dispersion time is 10-30 minutes.
4. A device used in the method for preparing the catalyst slurry according to any one of claims 1 to 3, comprising a grinding drum containing zirconium oxide beads, wherein the grinding drum is provided with a feed end and a discharge end, wherein: A feed cavity is provided at the feed end, a high-pressure pushing mechanism is provided in the feed cavity, a screen is provided at the feed end of the feed cavity near the grinding drum, and the screen is rotatably connected in the grinding drum; the discharge end of the grinding drum is connected to the feed cavity through a pipeline; The grinding drum body comprises an outer body and an inner body, a hollow cavity is formed between the outer body and the inner body, and a cooling circulating water pipe is arranged in the hollow cavity.
5. The device according to claim 4, characterized in that The cooling circulating water pipe surrounds the hollow cavity and is attached to the outer wall of the inner cylinder or the inner wall of the outer cylinder.
6. The device according to claim 4, characterized in that The pore size of the sieve is 100-200 microns.
7. A method for preparing catalyst slurry using the device according to any one of claims 4 to 6, characterized in that: The following steps are involved: S1, mixing the ionomer solution with an organic dispersant and a medium boiling point solvent to obtain a mixed solution; S2, mixing the catalyst with ultrapure water, and then adding the mixed solution to perform high-speed dispersion pretreatment to obtain a primary catalyst slurry; wherein the speed of the high-speed dispersion pretreatment is 5000-8000 rpm; S3, placing the primary catalyst slurry into the feed cavity of the grinding drum containing zirconium oxide beads, pushing the primary catalyst slurry to the screen by a high-pressure pushing mechanism, and controlling the rotation of the screen to achieve the cutting and dispersion of particle agglomerates in the catalyst slurry, and the catalyst slurry enters the grinding drum after high-pressure dispersion, and the zirconium oxide beads grind the catalyst slurry while the grinding drum rotates, and the grinding is performed at 3-8°C; S4, the primary catalyst slurry after grinding enters the feed chamber again through the pipe at the discharge end, and the catalyst slurry is obtained after repeating step S3 for 3-5 cycles.
8. The method according to claim 7, characterized in that In step S1, the medium boiling point solvent is one of n-butanol, toluene and cyclohexanone; The organic dispersant is one of isopropanol, ethanol and n-propanol.
9. The method according to claim 7, characterized in that: In step S3, the pressure of the high-pressure pushing mechanism is 20000-35000psi; The rotation speed of the screen is 2000-5000rpm; The size of the zirconia beads is 0.1-0.5 mm, the rotation speed of the grinding chamber is 3000-4000 rpm, and the grinding processing time is 15-40 minutes.
10. The method according to claim 7, characterized in that: In step S4, in each cycle, the rotation speed of the screen is 1.05-1.3 times that of the previous cycle; In each cycle, the pressure of the high-pressure pushing mechanism increases by 3000psi compared with the previous cycle.
Citation Information
Patent Citations
Fuel cell catalyst slurry directly coated on proton membrane as well as preparation method and application of fuel cell catalyst slurry
CN115692736A
Preparation method of anode catalyst slurry for PEM water electrolysis
CN117051419A
Cathode catalyst layer slurry and preparation method thereof, membrane electrode and fuel cell
CN117810465A
Vertical zirconium-bead grinder
CN202861975U
Whitewashed materials grinding device of circulated use
CN208066440U